Characteristics of empathy and psychopathy among pathological Internet users and opiate-dependent persons - jelkić, milica; Dolić, Mirko; Popović, Ivana; Nikolić, Bojan; Radulović, Igor; Kolundžija, Ksenija; mandic gajic, gordana (Vojnosanitetski pregled, 2020)
Background/Aim. The debate about diagnostic criteria for differences and similiraties as psychosocial characteristics of pathological Internet users and Internet and substance addicts still continued. The aim of the study was to investigate the differences between empathy and psychopathy among subjects with pathological Internet use (PIU) and opiate dependence.  Methods. The cross sectional study was performed at the Methadone Center of the Clinical Centre of Vojvodina, Novi Sad, Serbia, with 40 consecutively recruited patients with opiate dependence (OD group) and compared to age matched (25 to 35 years) random online recruited subjects (n = 80). They were divided into two groups: 40 subjects with PIU and 40 controls according to cut-off score of 39 or less obtained at Questionnaire regarding the Internet use assessment.  The questionnaires for sociodemographic data, Emotion Specific Empathy (EMI) questionnaire and Psychopathy Assessment Questionnaire (PAQ) were applied. Descriptive statistics, χ2-tests, ANOVA and MANOVA analysis were used for data assessment which was performed by the SPSS software (version 20.0) and p < 0.05 was applied. Results. There were more differences among psychopathy dimensions than empathy dimensions among PIU subjects, controls and heroin dependent subjects. The PIU group demonstrated the lowest psychopathy dimensions except for the lifestyle dimension which was higher than in the control group. On the contrary, the PIU group showed the highest empathy, with two dimensions as the most prominent ones: empathy with negative emotions and emotional reactions provoked by empathy. Conclusion. The PIU subjects are characterized by high empathy and low psychopathy. These findings suggest that it would be useful to consider seriously the dimensions of empathy and psychopathy when developing strategies to prevent PIU and planning educational programs for persons with problems related to the Internet overuse disorder.
Keywords: empathy; antisocial personality disorder, internet; opioid related disorders.